Mixed Oligoureas Based on Constrained Bicyclic and Acyclic β‐Amino Acids Derivatives: On the Significance of the Subunit Configuration for Folding. Issue 50 (6th November 2013) - André, Christophe; Legrand, Baptiste; Moulat, Laure; Wenger, Emmanuel; Didierjean, Claude; Aubert, Emmanuel; Averlant‐Petit, Marie Christine; Martinez, Jean; Amblard, Muriel; Calmes, Monique
Abstract The combination of a non‐functionalized constrained bicyclo[2.2.2]octane motif along with urea linkages allowed the formation of a highly rigid 2.512/14 helical system both in solution and the solid state. In this work, we aimed at developing stable and functionalized systems as promising materials for biological applications in investigating the impact of this constrained motif and its configuration on homo and heterochiral mixed‐oligourea helix formation. Di‐, tetra‐, hexa‐, and octa‐oligoureas alternating the highly constrained bicyclic motif of (R) or (S) configuration with acyclic (S)‐β3‐amino acid derivatives were constructed. Circular dichroism (CD), NMR experiments, and the X‐ray crystal structure of the octamer unequivocally proved that the alternating heterochiral R/S sequences form a stable left‐handed 2.5‐helix in contrast to the mixed (S/S)‐oligoureas, which did not adopt any defined secondary structure. We observed that the (−)‐synclinal conformation around the CαCβ bond of the acyclic residues, although sterically less favorable than the (+)‐synclinal conformation, was imposed by the (R)‐bicyclic amino carbamoyl (BAC) residue. This highlighted the strong ability of the BAC residue to drive helical folding in heterochiral compounds. The role of the stereochemistry of the BAC unit was assessed and a model was proposed to explain the misfolding of the S/S sequences.